Pengaruh Reward dan Punishment terhadap Kinerja Karyawan PT Ruijin Trade Indonesia Jaya - Siti Fatimah (Jurnal Publikasi Ilmu Manajemen, 2025)
Based on various literatures, reward can be understood as an award or reward given by an organization to its members, either in the form of financial, nonfinancial, or psychological material. This study aims to determine the influence of Reward and Punishment on Employee Performance of PT Ruijin Trade Indonesia. The data collection method for this study is the interview and questionnaire method, and the data analysis uses quantitative analysis. Based on the results of the T test that was conducted, the sig value was 0.014 from the T table value of 2.037, it was concluded that Punishment had a partial influence on employee performance. Based on the results of the F test conducted, the sig value is 0.000 the F table value is 4.149, so it is concluded that Reward and Punishment have a simultaneous influence on employee performance. Based on the results of the determination coefficient test (simultaneous) it shows that it is concluded that Reward and Punishment have an effect of 80%, while 20% is influenced by other variables that are not studied.